2016
DOI: 10.1152/ajplung.00357.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood-derived endothelial colony-forming cell function is disrupted in congenital diaphragmatic hernia

Abstract: Vascular growth is necessary for normal lung development. Although endothelial progenitor cells (EPCs) play an important role in vascularization, little is known about EPC function in congenital diaphragmatic hernia (CDH), a severe neonatal condition that is associated with pulmonary hypoplasia. We hypothesized that the function of endothelial colony-forming cells (ECFCs), a type of EPC, is impaired in CDH. Cord blood (CB) was collected from full-term CDH patients and healthy controls. We assessed CB progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Third, ECFCs’ angiogenic behavior is typically compromised in the presence of cardiovascular risk factors that predispose to the onset of ischemic disorders; this further contributes to discouraging the use of circulating ECFCs for autologous cell therapy [ 15 , 59 , 110 , 115 ]. For instance, the frequency and/or vasoreparative potential of circulating ECFCs are remarkably reduced with CAD [ 120 ], aging [ 121 ], diabetes [ 122 ], abdominal aortic aneurysm [ 123 ], venous thromboembolic disease [ 124 ], congenital diaphragmatic hernia [ 125 ], systemic lupus erythematosus [ 126 ], and the pediatric Moyamoya disease (MMD) [ 127 ]. In addition, ECFCs’ angiogenic behaviour is impaired in patients affected by human immunodeficiency virus (HIV), which has long been associated with cardiovascular disorders [ 128 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…Third, ECFCs’ angiogenic behavior is typically compromised in the presence of cardiovascular risk factors that predispose to the onset of ischemic disorders; this further contributes to discouraging the use of circulating ECFCs for autologous cell therapy [ 15 , 59 , 110 , 115 ]. For instance, the frequency and/or vasoreparative potential of circulating ECFCs are remarkably reduced with CAD [ 120 ], aging [ 121 ], diabetes [ 122 ], abdominal aortic aneurysm [ 123 ], venous thromboembolic disease [ 124 ], congenital diaphragmatic hernia [ 125 ], systemic lupus erythematosus [ 126 ], and the pediatric Moyamoya disease (MMD) [ 127 ]. In addition, ECFCs’ angiogenic behaviour is impaired in patients affected by human immunodeficiency virus (HIV), which has long been associated with cardiovascular disorders [ 128 ].…”
Section: Manipulation Of Pro-angiogenic Signaling Pathways To Imprmentioning
confidence: 99%
“…34,35 Endothelial colonyforming cells derived from cord blood of CDH newborns have blunted responses to VEGF and high levels of nitric oxide production, as well as reduced potential for proliferation and migration, which suggests a reduced number of both VEGF receptors in endothelial cells of CDH newborns. 36 Krüppel-like factor 2 (KLF-2), a central regulator of endothelial function, is known to mediate the VEGF-induced EC maturation. 37 In lungs of nitrofen-exposed fetuses with CDH, KLF-2 is downregulated.…”
Section: Factors Involved In Ec Dysfunctionmentioning
confidence: 99%
“…Hernia altered in CDH infants, but the mechanism is unknown [114]. Russo et al reported the use of transplacental sildenafil rescues lung abnormalities in a rabbit model of CDH, improves vascular branching, and reduces pulmonary vascular resistance [115].…”
Section: Discussionmentioning
confidence: 99%